Antimicrobial resistance research in a post-pandemic world: Insights on antimicrobial resistance research in the COVID-19 pandemic - Rodríguez-Baño, Jesús; Rossolini, Gian Maria; Schultsz, Constance; Tacconelli, Evelina; Murthy, Srinivas; Ohmagari, Norio; Holmes, Alison; Bachmann, Till; Goossens, Herman; Canton, Rafael; Roberts, Adam P.; Henriques-Normark, Birgitta; et al. (JOURNAL OF GLOBAL ANTIMICROBIAL RESISTANCE, 2021)
•Antibiotics have been used excessively in hospitalised COVID-19 patients.•COVID-19 has caused major disruptions to antimicrobial resistance surveillance and research.•Global data on the use of antibiotics during the COVID-19 pandemic are needed.•Antimicrobial resistance requires continued public and political engagement. Antimicrobial resistance must be recognised as a global societal priority - even in the face of the worldwide challenge of the COVID-19 pandemic. COVID-19 has illustrated the vulnerability of our healthcare systems in co-managing multiple infectious disease threats as resources for monitoring and detecting, and conducting research on antimicrobial resistance have been compromised during the pandemic. The increased awareness of the importance of infectious diseases, clinical microbiology and infection control and lessons learnt during the COVID-19 pandemic should be exploited to ensure that emergence of future infectious disease threats, including those related to AMR, are minimised. Harnessing the public understanding of the relevance of infectious diseases towards the long-term pandemic of AMR could have major implications for promoting good practices about the control of AMR transmission.